Evidence for a wide and gently dipping Main Himalayan Thrust in western Bhutan. Issue 9 (7th May 2015) - Le Roux‐Mallouf, Romain; Godard, Vincent; Cattin, Rodolphe; Ferry, Matthieu; Gyeltshen, Jampel; Ritz, Jean‐François; Drupka, Dowchu; Guillou, Valéry; Arnold, M.; Aumaître, G.; Bourlès, D. L.; Keddadouche, K.
Abstract The Main Himalayan Thrust (MHT) is the source of great earthquakes that have been documented along the range. Its geometry is a key parameter that influences accommodation of tectonic loading and earthquake magnitudes along the Himalayan Arc. Although seismic images are available for both the western and the central part of the range, this geometry remains poorly constrained for the Bhutanese Himalayas. Here we address this issue using a 10Be cosmogenic nuclides denudation transect across western Bhutan. We observe a wide low denudation rate domain between 50 km and 110 km from the front followed by a strong northward increase. Using a joint inversion of denudation rates, GPS data, and Holocene uplift rates, we interpret this pattern as a consequence of a flat‐ramp transition along the MHT. Compared to central Nepal and Sikkim, this location of the ramp suggests a wider décollement, with implications for greater seismogenic potential of the MHT in western Bhutan.